Penentuan Rute Terpendek dengan Menggunakan Metode Algoritma Clarke and Wright Savings - Damayanti, Dwi Kartika; Purnamasari, Ika; Wasono, Wasono (EKSPONENSIAL, 2021)
Operations research is a method regarding retrieval optimal decisions in the modeling of systems, both deterministic or probabilistic orginating from real life. One of the operations research methods is The Clarke and Wright savings algorithm, which is an exchange procedure, where a set of route at each step is exchange to get a better set of routes. This method is often referred to as a method. In this research, the Clarke and Wright savings algorithm is used to find out the distribution route and the minimum costs incurred on saving. On distribution of Bottled Water (AMDK) to determine how large savings that occur on the distribution route AMDK. Bottled Water (AMDK) is drinking water that is ready to be consumed directly without having to go through the heating process first. To determine the distribution route using the Clarke and wright savings method, a depot distance matrix is made to customer and from the customer to the customer and then continues to make the clarke and wright savings matrix. After searching for the shortest route using the clarke and wright savings method, the savings value is obtained to determine the customer’s route by sorting from the largest to the smallest value. In region 1 there were 5 trips with a total distance of 210.21 km, in region 2 there were 4 trips with a total distance of 191.35 km, in region 3 there were 5 trips with a total distance of 143.85 km, in region 4 there were 5 routes with a total distance 108.24 km, and in region 5 6 trips were obtained with a total distance of 113.95 km. The total distance travelled to deliver gallons to all routes is 767.59 km.